1980
DOI: 10.1172/jci109846
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Structure in Denatured DNA is Responsible for Its Reaction with Antinative DNA Antibodies of Systemic Lupus Erythematosus Sera

Abstract: A B S T R A C T Experiments were designed to determine the basis for the strong competitive reaction of denatured DNA with systemic lupus erythematosus (SLE) antinative DNA antibodies. Secondary structure in denatured DNA was reflected in hyperchromicity upon heating and in multiphase kinetics ofits digestion by Si nuclease. Partial digestion by Si nuclease completely eliminated the ability of denatured DNA to react with antidenatured DNA antibodies, but not its ability to react with SLE sera. Sl nuclease-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Either double-stranded polynucleotides or denatured DNA effectively compete with these antibodies for native DNA binding (24, 25, 28-30). These immunoglobulins may interact with portions of bases and/or polynucleotide backbone structures accessible in both forms of DNA (29,30). Some also react with phospholipids, which have no purine or pyrimidine base (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Either double-stranded polynucleotides or denatured DNA effectively compete with these antibodies for native DNA binding (24, 25, 28-30). These immunoglobulins may interact with portions of bases and/or polynucleotide backbone structures accessible in both forms of DNA (29,30). Some also react with phospholipids, which have no purine or pyrimidine base (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Some lupus autoantibodies react with denatured but not native DNA, whereas others react with both forms-usually better with the denatured DNA. Less common are antibodies with a true selectivity for the native form (9,11). As native DNA has not been an effective immunogen in experimental animals, the autoimmune subjects are the primary sources of antibodies that react with it.…”
mentioning
confidence: 99%
“…The high affinity anti-dsDNA antibodies did not bind significantly to ssDNA, which is unusual. Stollar & Papalian [28] have shown that ssDNA. prepared in a similar though not identical manner to the ssDNA we used, does maintain some secondary, native DNA-Iike structure.…”
Section: Discussionmentioning
confidence: 98%